2012
DOI: 10.1128/jb.06665-11
|View full text |Cite
|
Sign up to set email alerts
|

FdhTU-Modulated Formate Dehydrogenase Expression and Electron Donor Availability Enhance Recovery ofCampylobacter jejunifollowing Host Cell Infection

Abstract: bCampylobacter jejuni is a food-borne bacterial pathogen that colonizes the intestinal tract and causes severe gastroenteritis. Interaction with host epithelial cells is thought to enhance severity of disease, and the ability of C. jejuni to modulate its metabolism in different in vivo and environmental niches contributes to its success as a pathogen. A C. jejuni operon comprising two genes that we designated fdhT (CJJ81176_1492) and fdhU (CJJ81176_1493) is conserved in many bacterial species. Deletion of fdhT… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
27
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(28 citation statements)
references
References 89 publications
1
27
0
Order By: Relevance
“…We have shown here the need for selenium for FDH activity and that the Cj1500 (FdhT) and Cj1501 (FdhU) proteins are involved in FDH biogenesis, possibly by mediating selenium uptake or downstream processing. In an independent, concurrent study, Pryjma et al (28) show that in C. jejuni strain 81-176, the fdhTU genes are required for optimal recovery following invasion of epithelial cells, and their data confirm the role of the fdhTU genes in FDH biosynthesis and activity in a third reference strain of C. jejuni. Combined with earlier studies on formate metabolism and intestinal colonization studies and virulence of C. jejuni (2,34,42), this suggests an important contribution of FDH, and also FdhTU and potentially selenium in colonization and virulence properties of C. jejuni.…”
Section: Discussionmentioning
confidence: 52%
“…We have shown here the need for selenium for FDH activity and that the Cj1500 (FdhT) and Cj1501 (FdhU) proteins are involved in FDH biogenesis, possibly by mediating selenium uptake or downstream processing. In an independent, concurrent study, Pryjma et al (28) show that in C. jejuni strain 81-176, the fdhTU genes are required for optimal recovery following invasion of epithelial cells, and their data confirm the role of the fdhTU genes in FDH biosynthesis and activity in a third reference strain of C. jejuni. Combined with earlier studies on formate metabolism and intestinal colonization studies and virulence of C. jejuni (2,34,42), this suggests an important contribution of FDH, and also FdhTU and potentially selenium in colonization and virulence properties of C. jejuni.…”
Section: Discussionmentioning
confidence: 52%
“…In one such study (32), the C. jejuni genes fdhT and fdhU (encoding the proteins FdhT and FdhU of unknown function) were identified as crucial for the ability to recover these bacteria from standard growth media. Clearly, then, C. jejuni alters its metabolism under different environmental conditions to sustain its pathogenic and commensal modes of existence (32,33). It is possible that cecal proteases may have triggered bacterial switch to a VBNC state, a possible explanation for the reduced pglB mutant CFU recovered despite similar levels of live WT and pglB mutant cells.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, it has been shown that C. jejuni can switch into a "viable but nonculturable" (VBNC) state in response to stress (21,31). In recent studies (21,32,33), C. jejuni has been demonstrated to alter its metabolism in response to stress, leading to reduced culturability. In one such study (32), the C. jejuni genes fdhT and fdhU (encoding the proteins FdhT and FdhU of unknown function) were identified as crucial for the ability to recover these bacteria from standard growth media.…”
Section: Discussionmentioning
confidence: 99%
“…This gene has recently been annotated as fdhT, an accessory gene contributing to formate dehydrogenase expression and activity, probably by interfering with selenium metabolism (Shaw et al, 2012). Interestingly, the fdhTU operon (cj1500-1501) was crucial for recovery after invasion of Caco-2 cells, indicating a major role during infection (Pryjma et al, 2012). Altogether, these transcriptomic data demonstrate a role for Cj1000 in the regulation of respiratory pathways that are required for growth under lowoxygen conditions.…”
Section: Energy Metabolismmentioning
confidence: 59%